Anisakiasis Pada Ikan Laut Di Indonesia: Prevalensi, Sebaran Dan Potensi Patogenitasnya Pada Manusia - Forman Erwin Siagian; Esy Maryanti (Jurnal Ilmu Kedokteran, 2020)
Nematode worm Anisakis sp is the causative agent of anisakiasis, a zoonosis which continues to be a health problem in humans, globally. Its clinical spectum varies from mild to very severe and always connected with sea fishes, one important source of nutrition for the community that cannot be ignored. In addition, consumer’s behavior and lifestyle in processing and consuming sea fishes also have has the potency as the predisposing factor for its transmission and clinical manifestations. This review article aimed to describes recent global data on anisakiasis and its occurrence in marine fishes of Indonesian waters and the risk of transmission in the community.